A research and class model for future library instruction in higher education. Issue 9 (29th August 2014) - Kinsley, Kirsten; Hill, Leslie Brooke; Maier-Katkin, Daniel
Abstract : Purpose: Describes a university library instruction and research model that represents a collaborative effort between faculty, libraries, and the campus reading writing center. It utilizes rigorous research methods in order to measure whether the classroom intervention impacts student perceptions and success outcomes. Design/methodology/approach: Longitudinal, mixed-methods approach that attempts to measure the outcome of an experimental class that uses precision (exact) matching to control for extraneous variables that impact student success and a survey to measure student perceptions. Findings: Librarians can benefit by collaborating with faculty to learn more rigorous research methods. Precision (exact) matching a control group with an experimental group is time intensive, but easily replicated. Preliminary results are very promising for both the precision matching and the survey data. It appears that students are able to learn critical thinking, research, and writing skills from the collaboration between discipline-specific faculty, librarians, and reading writing center tutors. Research limitations/implications: Precision (exact) matching a control group with an experimental group is time intensive. Thus, the results need to be viewed cautiously due to the small sample size. Practical implications: Combining efforts to conduct collaborative research and instruction between libraries and faculty can provide resources for applications of the model with other disciplines. Originality/value: The library-intensive freshman writing seminar is a unique approach to student learning and an easy way for the library to be actively integrated in other disciplines. The precision matching technique is a methodologically rigorous research design that easy to replicate in other locations and with other disciplines.